Sustainability starts with Local Intervention - Belchior-Rocha, H.; Cardoso, Júlia ou Cardoso, Maria Júlia (European Association of Schools of Social Work. Conference Madrid 2019, 2019)
The operationalization of territorial social intervention is not separated from the models of welfare adopted by the States, from the debate about the meaning of community action and from the analysis and understanding of the problems in their interrelation with the global level and the national level, and with the economic, cultural and political dimensions inherent in these two levels. Therefore, this is a complex process in its development, both from the conceptual point of view, and from the point of view of the models and the social meaning of local intervention. In this study of explanatory nature and field research, we used mixed methods (surveys and semi-directive interviews); the observable universe consisted of socio-environmental intervention projects in socially vulnerable communities, with the presence of social workers, in multidisciplinary teams. We perceive that today, either because of weaknesses in the social protection system, in terms of its organization and functioning, or because of the inability to guarantee universal and sufficient coverage for financial reasons, because of the increasing number of long term unemployment, or even those who have never been part of the labour market, the care component of that system has become essential within the global system of protection, being reserved the role of guarantee of the rights of citizenship. The removal of obstacles, such as the absence of concerted social policies, the lack of updating and scientific knowledge, the difficulty of giving visibility to social issues, and the lack of instruments for evaluating the quality of the programs and the answers often prevent the achievement of the objective of social intervention: the promotion and effectiveness of the quality of life and well-being of individuals and communities and sustainable development that must be perceived in social work education and training.